RASIO PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN STUDI KASUS PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Subaida, Ida; Muslimatus, Riza Nur; Aprilia, Cindy Pamela (Growth, 2025)
This study aims to analyze profitability ratios to measure the financial performance of companies in the banking sector during the 2022–2024 period. The research method employed is descriptive quantitative analysis using secondary data in the form of financial statements of banking companies for the 2022–2024 period. The profitability ratios analyzed include return on assets (ROA), return on equity (ROE), and net profit margin (NPM).The results of the analysis indicate that, in general, the banking sector exhibits ROA levels classified as very good, suggesting that banks are able to manage their assets effectively to generate profits. However, the ROE and NPM ratios fall into the very poor category, reflecting low returns on equity and suboptimal efficiency in converting revenue into net profit